An exploration of the use of MOCCs for Malaysian teacher's professional development - Misrah Hamisah Mohamed
T!lis thesis is a presentation of a project undertaken to explore the contribution that Massive Open Online Courses (MOOCs) can make to the professional development of Malaysian teachers who teach English as a second language in school and higher education institutions. MOOCs are seen as a platform with huge potential in this field, but their application is subject to the accessibility of teacher networks, suitability of course structures and organisation, challenges in the transferability of knowledge and skills, teachers' readiness in using MOOCs and the opportunities and constraints which the work and family context provides. This thesis includes observations of ten newly available MOOCs and interviews with 14 Malaysian MOOC participants. The ten MOOCs observed are from existing providers: NovoEd, Coursera, FutureLearn and Canvas. They were analysed and compared using a matrix with three main focuses: pedagogy, content materials, and assessment. 14 participants were later recruited as volunteer participants in these MOOCs. All 14 were currently teaching or planning to teach ESL in Malaysia. Their responses were coded and analysed using qualitative analysis software, Mltls.ti. Rci.alising how important it was to find out the context where the participants worked, a series of etlhnographic style observations were also carried out. The data gained was coded and analysed ussing Atlas.ti too. The findings revealed that all ten courses corresponded to the idea of an xMOOC, in that they were run on a model of instructional design. However, in terms of the degree of openness, the MOOCs differed. They were more or less open, or simply contained, depending on how they were pedagogically organised, the materials provided, and the way the assessment was conducted. Reflecting on the participants' responses, all the MOOCs used had the potential to be an effective medium for teachers' CPO because they had the characteristic of an ideal CPO programme. Further. they offered teachers certification. rooms for informal learning and the flexibility that a CPO programme cannot offer. However. MOOCs are found to be difficult to' fit into the Malaysian EFL teachers' context because the participants had other things going on in their lives. Further investigation revealed that the participants valued the physical presence of others and thought they learned more by having the face-to-face conversation. Thus. a hybrid of MOOCs and face-to-face interaction seemed to be a logical solution to promote CPO. The study succeeded in showing the value and variation in MOOCs and the opportunity for providing teachers with a desirable CPD programme. thus demonstrating the range of possibilities open to course designers and providers. Through careful consideration of the key characteristics of an ideal CPO programme. along with an opportunity to create a community of practice online and offline. a hybrid MOOC could be designed and implemented to best meet teachers' local and contextual needs. Such an approach could generate positive change among schools. students. and even the education system at large.